Enhanced arsenic removal from water by mass re-equilibrium: kinetics and performance evaluation in a binary-adsorbent system. (15th February 2021) - Wang, Zhengyang; Liao, Peng; He, Xiaoqing; Wan, Peng; Hua, Bin; Deng, Baolin
Highlights: A new mass re-equilibrium (MRE) process was proposed and evaluated for As removal. The MRE process was configured to allow transfer of As between two media. As could diffuse from a fast-uptake medium to a slow-adsorbing but high-affinity one. Desorbed amounts were dependent on the adsorption capacity differences of two media. Packed column with the mixed-medium approach showed MRE could improve As removal. Abstract: Because arsenic (As) is highly toxic and carcinogenic, its efficient removal from drinking water is essential. Considering some adsorption media may adsorb As fast but are too expensive to be applied in a household, while others could be abundantly available at low cost but with slow uptake kinetics, we explored a novel mass re-equilibrium (MRE) process between two media with different adsorption characteristics to enhance the overall As removal. We employed an adsorbent with fast adsorption kinetics to grab As from water, and then allow it to transfer to a second adsorbent with large capacity for As retention. In the system containing two adsorbents separated by a dialysis membrane, the results showed that As associated with a fast-adsorbing iron-based ordered mesoporous carbon could diffuse to a slow-adsorbing but high-capacity iron-based activated carbon. Column tests were further conducted, showing that the mixed medium, composed of the two adsorbents, could be used to adsorb As at a very short empty bed contact time (≤ 1 min) and the removal was improved by the MRE that potentially redistributed solid-phase As during pump-off periods. This study points to a new direction that by the MRE process, novel binary-adsorbent approaches may be developed for contaminant removal, if suitable media and process configuration could be identified. Graphical Abstract: Image, graphical abstract